The relationship between nutrition and Meniere's disease - CEBECİ, AYBİKE; GEÇİCİ, CENNET REYYAN; OĞUZ, ESMA (ELSEVIER SCI LTD, 2021)
Meniere's disease is an inner ear disease with attacks characterized by ear fullness, tinnitus, fluctuant sensorineural hearing loss and vertigo. Although pathophysiology of the disease is not fully known, endolymphatic hydrops are believed to play a role. Although there is no certain treatment procedure for Meniere's disease, some treatments are applied to prevent attacks, to treat the symptoms that occur during the attacks, and to prevent the permanent effects of the symptoms on the hearing and balance system. Lifestyle changes, dietary modifications, diuretics, vasodilator corticosteroids, intratympanic steroids, surgical methods are some of these treatment methods. Dietary modification includes a low sodium diet, a reduction in daily alcohol and caffeine intake, a gluten-free diet, and a new dietary approach to specially processed grains, all of which are first-line treatments. The goal of this review article is to examine the relationship between MD and dietary intervention, which is frequently used in the prevention and treatment of MD attacks. (C) 2021 Oto-Rhino-Laryngological Society of Japan Inc. Published by Elsevier B.V. All rights reserved.
Keywords: Meniere's disease; Endolymphatic hydrops; Low sodium intake; Gluten free diet; Allergy; QUALITY-OF-LIFE; ANTISECRETORY FACTOR; THERAPY IMPROVES; EXPRESSION; ALLERGY; EPIDEMIOLOGY; MANAGEMENT; SYMPTOMS; ALCOHOL; WATER